THE EFFECT OF E-WOM ON DESTINATION IMAGE AND ATTITUDE TOWARDS TO THE VISIT INTENTION IN KOMODO NATIONAL PARK, INDONESIA - Septi Fahmi Choirisa; Purnamaningsih Purnamaningsih; Yoanita Alexandra (Journal of Tourism Destination and Attraction, 2021)
This study aims to identify the theoretical arguments and hypotheses regarding the interrelationships among the electronic word of mouth (E-WOM), destination image, and tourist attitudes towards the visit intention when the Government has a new membership policy for visiting the Komodo National Park Indonesia. A total of Trip Advisor users, as many 388 online respondents participated in this study. Data were obtained from the online survey using a questionnaire with a Likert Scale. We evaluated the data using the Structural Equation Model (SEM) analysis and employed the Partial Least Square to assess the validity, reliability, and examine the hypothesis. The findings confirm this study reveals that E-WOM is significant in affecting the image destination and tourist attitudes that will affect to the visit intention. This result of this study will contribute to the field of e-commerce marketing, destination branding, tourism destination, and e-tourism research. This study helps tourism organizations in the development and implementation of destination marketing strategies in Indonesia. Keywords: E-WOM, tourism destination, attitude, visit intention, and Komodo National Park.